PENINGKATAN EFEKTIVITAS PELAYANAN PUBLIK MELALUI PENGEMBANGAN SISTEM PENGARSIPAN DIGITAL PADA SEKSI KESEJAHTERAAN MASYARAKAT KANTOR CAMAT PARLILITAN - Nova Claudya Lubis; Lastri (DEVELOPMENT: Journal of Community Engagement, 2026)
The archiving and service administration system plays a crucial role in supporting the effectiveness and efficiency of government officials, particularly at the sub-district level. This study aims to analyze the archiving and service administration system in the Community Welfare Section of the Parlilitan Sub-district Office. The method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that the archiving system still uses a combination of manual and semi-digital systems, which is not yet fully optimal. While service administration has been running quite well, there are still obstacles such as limited facilities and infrastructure, low utilization of information technology, and limited human resources in archive management. These conditions impact the slow process of searching for certain documents. A well-organized archiving system has been proven to accelerate public services and improve administrative accountability. Therefore, it is necessary to increase the capacity of the apparatus, develop a digital-based archiving system, and provide supporting facilities to improve the quality of public services.